جمالية توظيف الأشكال الأجناسية في الاستهلال الشّعري -ديوان "أعراس الملح"للشّاعر عثمان لوصيف أنموذجا - مزروع , الطاهر; شبرو, عبد الكريم (My University, 2024)
تهدف هذه الورقة البحثية إلى الوقوف على عتبة الاستهلال في القصيدة العربية المعاصرة؛ والكشف عن أبعاده الفنّية والجمالية في ديوان "أعراس الملح" للشاعر عثمان لوصيف؛ من خلال دراسة أهم الأشكال الأجناسية التي وُظّفت في الديوان، وأهمّ البناءات الهندسية والفنية التي شكّلت معالمه. This research paper aims at standing on the threshold of the beginning of the contemporary Arabic poem; revealing the artistic and aesthetic dimension in the divan of "Salt weddings" of poet Othman Losif, through studying the most important , genre forms employed in the divan, and the most important architectural and artistic structures that formed its features
The Aesthetic Of Employing Gender Forms In The Poetic Initiation, The Case Of Othman Lossif’s Aras Al-milh
مقال. مجلة القارئ للدراسات الأدبية والنقدية. مج07 . ع.01. جامعة الوادي
Keywords: استهلال; أشكال أجناسية; تشكيل بصري; دراما شعرية; Initiation; foreign forms; visual formation; poetic drama